Association of gene polymorphisms in the anti-Müllerian hormone signalling pathway with ovarian function: a systematic review and meta-analysis. Issue 3 (September 2019) - Cheng, Ran; Xiong, Wei; Luo, Xiaoyan; Ma, Yaxian; Nie, Ying; Qiao, Xiaoyong; Chen, Hui; Hu, Ying; Xu, Liangzhi
Abstract: This systematic review evaluated whether single nucleotide polymorphisms of AMH and AMHRII genes are associated with ovarian function. A literature search of PubMed and Embase was complemented by hand searches in the reference lists. Eight studies involving 3155 participants were included in a meta-analysis and 10 studies included for description. For AMH c.146T>G polymorphism, no significant difference in serum anti-Müllerian hormone (AMH) levels was found between participants with different genotypes (weighted mean difference [WMD] 0.42, 95% confidence interval [CI] −0.16 to 0.99). Subgroup analyses showed similar results for the European region and in healthy and infertile populations. Regarding AMHRII −482 A>G, there was no significant difference in serum AMH levels between participants with A/A genotype and G/A or G/G genotype carriers (WMD –0.04, 95% CI −0.31 to 0.23). In subgroup analysis, an interesting trend was confirmed in healthy women and polycystic ovary syndrome (PCOS) patients (WMD –0.36, 95% CI −0.63 to –0.09, P  = 0.009; WMD 0.46, 95% CI 0.15 to 0.77, P  = 0.004). The review suggests that AMH c.146T>G is not associated with AMH levels, while AMHRII −482 A>G may be related to AMH levels in PCOS and healthy subgroups. However, the impact of polymorphisms in the AMH signalling pathway on ovarian function still requires further investigation.